Debates over Dirigisme during the 1930s: The Case of Bulgaria. Issue 3 (3rd July 2019) - Penchev, Pencho D.
Abstract: During the 1930s and early 1940s, the problems of economic dirigisme and its theoretical analysis attracted the attention of Bulgarian economists. To some extent, it was compensation for the fact that they missed the socialist calculation debate of the interwar period. Their analyses were placed within the framework of a demand and supply core, combined with various other theoretical approaches. The Bulgarian academic economists identified a number of problems associated with the long-term functioning of the regulated economy: impossibility of the state apparatus to control spontaneous market forces by means of governmental regulation, inherent administrative constraints for government and public officials to introduce and control strict and conscientious implementation of all the laws and normative acts of the system of economic dirigisme, etcetera. A new theory of international trade was developed, the author of which attempted to break away from the old-fashioned labor theory of value. The main content of his concept lies in the claim that protectionism, in certain cases, may have positive economic consequences.